A trial of a six‐month sugar‐sweetened beverage intervention in secondary schools from a socio‐economically disadvantaged region in Australia - Jia Ying Ooi; Luke Wolfenden; Sze Lin Yoong; Lisa M. Janssen; Kathryn Reilly; Nicole Nathan; Rachel Sutherland (Elsevier, 2021)
Abstract Objective: This study assessed the effectiveness of a school‐based intervention in reducing adolescents' sugar‐sweetened beverage (SSB) consumption and percentage of energy from SSBs. Secondary outcomes were SSB consumption within school, average daily energy intake, and body mass index z‐scores. Methods: Six secondary schools located in New South Wales, Australia were recruited to participate in a six‐month pilot randomised controlled trial (1:1). The intervention included components targeting the school nutrition environment, curricula and community. Outcomes were collected via online surveys, observations, anthropometric measurements and project records. Between‐group differences were assessed via linear mixed models. Results: At the six‐month intervention endpoint (n=862) there were no statistically significant differences between students in intervention or control schools for mean daily intake of SSBs (8.55mL; CI −26.77, 43.87; p=0.63), percentage daily energy from SSBs (0.12% kJ; CI −0.55, 0.80; p=0.72), or for secondary outcomes. Acceptability of the school‐based strategies were high, however intervention fidelity varied across schools. Conclusion: While acceptable, improving fidelity of implementation and increasing the duration or intensity of the intervention may be required to reduce SSB intake. Implications for public health: Engaging parents and education stakeholders in the development phase to co‐design interventions may prove beneficial in improving intervention fidelity and enhance behavioural outcomes.